Covalent assembly of gold nanoparticles : an application toward transistor memory - Gupta, Raju Kumar (2013)
This work reports a versatile approach utilizing covalent assembly of functionalized gold nanoparticles for organic field-effect transistor (OFET) based memory devices. 11-Mercapto-1-undecanol functionalized gold nanoparticles (AuNPs) having size of 5 ± 0.5 nm were synthesized and immobilized onto SiO2 substrate through covalent binding using a functionalized polymer as a surface modifier. The pentacene OFET-based memory devices utilizing such covalently bound gold nanoparticles with nanoparticle density of 5 × 1011 cm–2 exhibited a large memory window (7.7 V), high on/off ratio between memory states (105), and long retention time (>10 000 s). The present synthetic route for memory devices incorporating covalently immobilized gold nanoparticles has several advantages such as solution processable, enhanced device stability, low-cost, and low-temperature process and will be a step toward realization for low-cost, lightweight, flexible, logic display driver, and flash memory applications.